Synthesis Of a Fe2o3 Nanowires/MWCNTS Composite For Photocatalyst - Mohd Suan, Mohd Shahadan; Ahmad, Nurulnabilah; Ismail, Syahriza; A. Bakar, F. I. (Institute of Physics Publishing, 2018)
Multi-walled carbon nanotube (MWCNTs) was decorated on nanowires iron oxide (α-Fe2O3) thin film (α-Fe2O3/MWCNTs) by spin coating method.Nanowires hematite was produced by thermal oxidation of Fe substrate at 400 °C for 120 minutes.The aim of this nanocomposite α-Fe2O3/MWCNT is to improve the photocatalytic efficiency of the α-Fe2O3 nanowires.The structural characterization of the as-prepared composites were analyzed by x-ray diffraction (XRD),raman spectra,and photoluminescence spectra (PL) to identify the structure of pure α-Fe2O3 and decorated of MWCNTs.While,the morphological observation,interaction of MWCNTs and nanowires structure on hematite phase was done by scanning electron microscopy (FESEM).It was found that,the optimization dispersion of MWCNTs in the dimethyl form amide (DMF) solvent through acid treatment with 3 Molar nitric acid (HNO₃),shows the homogenized well-decorated MWCNTs on the surface of the nanowires structure,which can eliminate the limitation of iron oxide and help in electron transfer from α-Fe2O3 to MWCNTs.